2021
DOI: 10.3390/nu13061828
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Agarophyton chilense Oleoresin Containing PPARγ Natural Ligands with Insulin-Sensitizing Effects in a C57Bl/6J Mouse Model of Diet-Induced Obesity and Antioxidant Activity in Caenorhabditis elegans

Abstract: The biomedical potential of the edible red seaweed Agarophyton chilense (formerly Gracilaria chilensis) has not been explored. Red seaweeds are enriched in polyunsaturated fatty acids and eicosanoids, which are known natural ligands of the PPARγ nuclear receptor. PPARγ is the molecular target of thiazolidinediones (TZDs), drugs used as insulin sensitizers to treat type 2 diabetes mellitus. Medical use of TZDs is limited due to undesired side effects, a problem that has triggered the search for selective PPARγ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…These receptors play a significant role in the regulation of transcription, energy and lipid metabolism, and thermogenesis (Lee et al, 2020). One study identified a specific type of MGDG in which the acyl groups acted as a potent PPAR-γ (peroxisome proliferator-activated receptor γ) ligand (Figure 6) (Pinto et al, 2021). These studies suggest that algal-derived glycerolipids might be considered potential activation targets of the PPAR family, indicating the need for further in-depth analysis of marine algae and their natural products.…”
Section: Treatment Of Metabolic Diseasesmentioning
confidence: 99%
“…These receptors play a significant role in the regulation of transcription, energy and lipid metabolism, and thermogenesis (Lee et al, 2020). One study identified a specific type of MGDG in which the acyl groups acted as a potent PPAR-γ (peroxisome proliferator-activated receptor γ) ligand (Figure 6) (Pinto et al, 2021). These studies suggest that algal-derived glycerolipids might be considered potential activation targets of the PPAR family, indicating the need for further in-depth analysis of marine algae and their natural products.…”
Section: Treatment Of Metabolic Diseasesmentioning
confidence: 99%
“…Red algae, particularly those of the genus Gracilaria , have been described as a complex lipid composition of glycerolipids, omega-3 and omega-6, and oxylipin-like fatty acids [ 4 , 5 ]. In the case of Gracilaria chilensis (known as Pelillo), essential fatty acids, such as polyunsaturated fatty acids (PUFA) have been described [ 6 , 7 , 8 , 9 ]. Recently, our laboratory reported that Gracilex ® , an oleoresin derived from G. chilensis , was enriched in palmitic acid, arachidonic acid, oleic acid, and lipophilic antioxidants such as tocopherols and β–carotene [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Gracilaria chilensis (known as Pelillo), essential fatty acids, such as polyunsaturated fatty acids (PUFA) have been described [ 6 , 7 , 8 , 9 ]. Recently, our laboratory reported that Gracilex ® , an oleoresin derived from G. chilensis , was enriched in palmitic acid, arachidonic acid, oleic acid, and lipophilic antioxidants such as tocopherols and β–carotene [ 9 ]. Gracilex ® can reduce metabolic alterations (increases in basal glucose and insulin levels) in mice fed with a high-fat diet [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Red algae such as G. chilensis are an excellent source of healthy essential fatty acids and other phytochemicals with bioactivities including antidiabetic, anti-inflammatory, antioxidant, and anti-neurodegenerative effects [ 2 , 10 , 11 , 12 ]. Recently, our laboratory reported that Gracilex ® , an oily extract derived from “Pelillo”, can reduce metabolic alterations (increases in basal glucose and insulin levels) in mice fed a high-fat diet [ 13 ]. Thus, the development of a nutraceutical derived from G. chilensis offers an opportunity to find other uses for this alga to diversify the productive matrix of the country, increasing the added value of G. chilensis biomass.…”
Section: Introductionmentioning
confidence: 99%